Efforts to Encourage Development of Sustainable Modern Agriculture Through Empowerment of Farmer Group - Khoirul Anam; Teguh Soedarto (Agricultural Science, 2022)
Modern agriculture activities by intensively cultivating land and the massive use of fertilizer and pesticide have been shown to significantly increase agricultural productivity. However, modern agricultural systems have a serious impact on environmental damage, so it is necessary to develop modern agricultural systems that are environmentally sound and sustainable. This agricultural system can be successful if it is supported by all stakeholders, especially the Farmer Groups as a forum for farmers in their agricultural activities. The powerlessness of farmer groups in managing their members and their farms can be the cause of the failure of sustainable development of modern agriculture. This study aims to describe and analyze efforts to encourage the development of a modern sustainable agricultural system through the empowerment of farmer groups. This research was conducted with a qualitative approach based on literature studies from several journals and the results of previous research. The study results indicate that empowerment of farmer groups is the right way to increase the participation of farmer communities in the development of sustainable modern agriculture. The empowerment process carried out with the awareness, capacity and empowerment of farmer groups can increase awareness, ability, expertise and strength to take advantage of their potential. In the empowerment activities, it is necessary to empower actors from local government, community leaders and farmer group leaders who can act as motors and motivators. In addition, it is necessary to anticipate the inhibiting factors and the supporting factors that can encourage farmer group empowerment activities.